2021
DOI: 10.1108/jpbm-05-2020-2899
|View full text |Cite
|
Sign up to set email alerts
|

City brand love: modelling and resident heterogeneity analysis

Abstract: Purpose This study aims to investigate how city dependence and city social bonding determine city brand love. In addition, the study examines whether there are different resident segments that exhibit distinct behaviour in relation to city brand formation. Design/methodology/approach The study is based on primary responses collected from 595 residents from Khulna city in Bangladesh. The research model is tested using partial least square (PLS) structural equation modelling. The resident segments were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 128 publications
1
6
0
Order By: Relevance
“…This is consistent with the finding that city-related attributes influence city identification (Shafiee et al, 2021). Finally, these results also clarify inconsistent conclusions in the literature about whether satisfied or dissatisfied tourists are more likely to engage in WOM (Sadeque et al, 2022). In fact, the scope of WoM is a major consequence of city brand love, espousing the view that discontented tourists actively engaged in negative WoM.…”
Section: Theoretical Contributionsupporting
confidence: 87%
See 3 more Smart Citations
“…This is consistent with the finding that city-related attributes influence city identification (Shafiee et al, 2021). Finally, these results also clarify inconsistent conclusions in the literature about whether satisfied or dissatisfied tourists are more likely to engage in WOM (Sadeque et al, 2022). In fact, the scope of WoM is a major consequence of city brand love, espousing the view that discontented tourists actively engaged in negative WoM.…”
Section: Theoretical Contributionsupporting
confidence: 87%
“…Tourism literature has shown that a memorable tourism experience can form strong emotional bonds (Ardyan and Susanti, 2018). As reported in previous studies, tourists can express love for the city they have visited (Insch and Walters, 2018;Sadeque et al, 2022). Shafiee et al (2021) underlined the positive effect of the cognitive and emotional dimensions and evaluated tourist-destination identification on love for the destination.…”
Section: City Brand Identification Memorable City Brand Experience An...mentioning
confidence: 64%
See 2 more Smart Citations
“…To attract new residents, investors and other stakeholders, place marketing and branding have become an important part of the overall city’s marketing strategy. The focus is now on providing an “experience” to the residents by creating better quality facilities and a place to create social bonds with other residents (Sadeque et al , 2021). RAB is seen as a cost-effective and efficient way to promote a city compared to traditional advertisements (Wassler et al , 2021).…”
Section: Introductionmentioning
confidence: 99%